Occurrence of Natural Vertical Transmission of “Zika like Virus” in Aedes aegypti Mosquito in Jambi City - Satoto, Tri Baskoro; Pasca Wati, Nur Alvira; Purwaningsih, Wida; Josef, Hari Kusnanto; Purwono, Purwono; Rumbiwati, Rumbiwati; Hermanto, Hermanto; Frutos, Roger (Kesmas, 2019)
Zika virus can be transmitted through mosquitoes such as Aedes aegypti and Ae. albopictus. During the transition period of 2014–2015, an outbreak of dengue was reported in Jambi City, during which several sufferers were screened positive for Zika virus infection by the Eijkman Institute. It was interesting to note that all of those positive for Zika virus infection were indigenous residents and none of them had a history of international travel. This descriptive analytic study with a cross-sectional design study was conducted to present an overview of Aedes spp. population using ovitrap and egg colonization methods and to detect the presence of Zika virus. Samples were analyzed using reverse transcription polymerase chain reaction for detection of Zika “like” virus and the mapping results were described. The Ovitrap Index was 44.74%, and examination of egg colonization collected from 40 neighborhoods revealed the presence of Zika “like” virus in samples obtained from the fourth neighborhood in Talang Bakung village. This result indicates the occurrence of natural vertical transmission of Zika “like” virus in A. aegypti mosquito in Jambi City, which potentially resulted in an outbreak.